Rapid screening for Schistosoma mansoni in western Côte d'Ivoire using a simple school questionnaire - J. Utzinger; E.K. N'Goran; Y.A. Ossey; M. Booth; M. Traoré; K.L. Lohourignon; A. Allangba; L.A. Ahiba; M. Tanner; C. Lengeler
The distribution of schistosomiasis is focal, so if the resources available for control are to be used most effectively, they need to be directed towards the individuals and/or communities at highest risk of morbidity from schistosomiasis. Rapid and inexpensive ways of doing this are needed, such as simple school questionnaires. The present study used such questionnaires in an area of western Côte d'Ivoire where Schistosoma mansoniis endemic; correctly completed questionnaires were returned from 121 out of 134 schools (90.3%), with 12 227 children interviewed individually. The presence of S. mansoni was verified by microscopic examination in 60 randomly selected schools, where 5047 schoolchildren provided two consecutive stool samples for Kato-Katz thick smears. For all samples it was found that 54.4% of individuals were infected with S. mansoni. Moreover, individuals infected with S. mansoni reported ''bloody diarrhoea'', ''blood in stools'' and ''schistosomiasis'' significantly more often than uninfected children. At the school level, Spearman rank correlation analysis showed that the prevalence of S. mansoni significantly correlated with the prevalence of reported bloody diarrhoea (P = 0.002), reported blood in stools (P = 0.014) and reported schistosomiasis (P = 0.011). Reported bloody diarrhoea and reported blood in stools had the best diagnostic performance (sensitivity: 88.2%, specificity: 57.7%, positive predictive value: 73.2%, negative predictive value: 78.9%). The study, which is probably the largest of its kind ever undertaken in Africa, revealed a moderate diagnostic performance of questionnaires for identifying individuals and/or communities at high risk from S. mansoni.